Greek medical professionals approaches and understanding of health literacy: a qualitative study - Eleni Louizou; Nikolaos Panagiotou; Εmmanouil Smyrnakis; Savvas Anastasiadis; Konstantinos G. Diamantis; Foivos Papamalis; Panagiotis D. Bamidis (BMC, 2023)
Abstract Background Health literacy holds significant importance for medical professionals, as it is widely acknowledged as a key element in enhancing health promotion and overall well-being. The primary objective of this study is to explore Greek physicians' comprehension of health literacy, the significance they attribute to it, their strategies for addressing patients with low health literacy, and the potential barriers they face while striving to enhance a patient's health literacy. In this context, we examine the communication methods employed by physicians as an integral part of their approach to improving a patient's health literacy. Methods A qualitative study was conducted between April 29, 2021, and February 17, 2022, utilizing in-depth, semi-structured interviews with 30 Greek medical professionals, of whom 15 were university professors. The research sample selection methodology employed in this study was purposive sampling. Data analysis was conducted using inductive thematic analysis. Results The majority of physicians were not familiar with the concept of health literacy. The most significant barriers to the development of health literacy among physicians are a lack of time, issues within the healthcare system, and interference from third parties, although they acknowledge that a significant portion of the responsibility lies with them. Effective communication with patients is important for all physicians, as it plays a crucial role in the therapeutic process. When they realize that their patients are not understanding them, they employ communication methods such as using plain language, providing numerous examples, incorporating visuals like pictures and even using drawings. Conclusions The findings of this study underscore the importance of implementing targeted initiatives to promote health literacy within the Greek medical and academic community. Integrating health literacy training for physicians into the educational and training curriculum is essential. To accomplish this goal, it is imperative to first address the shortcomings within the healthcare system and improve the working conditions for physicians.